Association between Preparatory Knee Muscle Activation and Knee Valgus Angle during Single Leg Cross Drop Landing Following Anterior Cruciate Ligament Reconstruction - Shadan Mohammadpour; Reza Rajabi; Hooman Minoonejad; Ali Sharifnezhad (Shiraz University of Medical Sciences, 2019)
Background: Knee valgus angle seems to be a key factor in both primary- and second-ACL injury risk models. The control of the alignment of the lower limb during dynamic movements depends on the neural activation of the muscles crossing the knee joint prior to the occurrence of stressful events. The current study examined the relationship between the preparatory knee muscle activity and knee valgus angle. Methods: Twenty-eight ACL reconstructed (ACLR) athletes were asked to perform three trials of a single-leg cross drop landing (SCD). Lower extremity kinematics and surface EMG were recorded. Initial contact knee valgus angle and EMG from 100 ms prior to ground contact were used in the data analyses. Results: Preparatory activation medial and lateral hamstring muscles were found to be negatively correlated with knee valgus angle at initial contact (P<0.05). However, the preparatory activity of vastus medialis and vastus lateralis muscles was not associated with initial contact knee valgus angle (P>0.05). Conclusion: The preparatory activity of the knee muscles is linked to knee valgus angle at initial contact, and it may indicate a potential target of second ACL injury prevention programs.